Cataloguing of Arabic materials - Suja', Balqis (2005)
This is a one day programme to give initial exposure on Arabic cataloguing. Topics covered are: 1)Transliteration; 2) Arabic name authority; 3) Technical reading; 4) Searching the online catalogue; 5) Bibliographic relationships; 6) Subject analysis; 7) Creating the catalogue record; 8) Shelflisting; 9) Bibliographic and cataloguing tools (AACR2R and its associate references; ALA-LC Romanization tables; LCSH and its associate texts; LCC scheme; Zirikli’s al-A’lam; Brockelmann; and Mu’jam al-mu’allifin). Impromptu hands-on learning was provided throughout the session.